Success Rate of User Education Programs in Institut Teknologi Sepuluh Nopember Library for Final-year Student - Izzah, Dwi Khusniatul (Universitas Airlangga, 2021)
The user education program is one of the university library's efforts in improving the information literacy skills of users, especially students. The user education program aims to guide students so that they can take advantage of the library and carry out information searches effectively and efficiently. In general, user education programs in university libraries are intended for all users, but some programs are intended for students, including final-year students. This research uses a descriptive quantitative research method, with purposive random sampling method as the sampling method, and final-year students of the Institut Teknologi Sepuluh Nopember as the research population. The research was conducted using Kirkpatrick's program effectiveness model, in which the effectiveness of a program can be determined through four levels, namely reaction, learning, behavior, and results. The results showed that three of the four levels were in the high category, while there was one level that was in the medium category, to be specific the behavior level. On the whole, the user education program at the Library of Institut Teknologi Sepuluh Nopember has been effective, but there is attention needed to service accessibility so that what users have learned in the program can become a habit and have a high level of behavior as an